Holdstock, Dick. Again With One Voice: British Songs of Political Reform, 1768-1868. Loomis House Press, 2021. 398 pp. ISBN 978-1-935243-77-9 - Rouse, Andrew C. (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Compilations of political ballads are nothing new. After all, practically from the earliest days of the broadside trade, they were seen as at least in part serving a journalistic role, and what is journalism at its best if not the voice of criticism of all aspects of life, whether of capital punishment, matrimonial infidelity, turncoat allegiances or merely unseemly new fashions. What makes Dick Holdstock’s book an especially welcome addition to the bookshelves of the ballad collector and social-political historian alike is the manner of its inception: “This book arose out of my curiosity about why, throughout the English-speaking world, there are so many songs in the repertoires of traditional British folk music performers that admire Britain’s historically accepted enemy, Napoleon Bonaparte” (Preface xi.). Setting aside the anomaly of traditional British singers ranging all over the English-speaking world, the phenomenon is after all not so strange. Successive British governments raised taxes to finance military operations both on land and at sea, and while the Royal Navy partly existed on the system of sharing out captured enemy ships, maintaining a large, trained land army was extremely draining on the country. It is not so illogical for the hungry, underpaid native, the family of the press-ganged breadwinner, to cast the blame not on the foreign foe but domestic taxation. Moreover, France was undergoing drastic political changes that certainly appealed to many parts of society.